H2O2-Responsive prodrug-nanosystem based on auto-fluorescent perylenetetracarboxylic diimide hinders the foaming progress in RAW264.7 cells. Issue 15 (17th March 2022) - Li, Zhi; Xue, Changning; Zhang, Lifen; Zhang, Yuman; Yu, Yao; Liu, Qianrui; Guo, XinHong; Zhang, ZhenZhong
Abstract : Schematic of the synthesis and functional mode of the H2 O2 responsive prodrug-nanosystem. HA–PBI–Tre can respond to H2 O2, release model drug, and inhibit the foaming progress. Abstract : Oxidative stress can lead to a variety of diseases, and oxalate bonds can consume excess reactive oxygen species (ROS) in cells. In this study, a H2 O2 -responsive prodrug-nanosystem was synthesized using oxalate-bond-connecting water-soluble drugs (Tre) with a fluorescent indicator (PBI). The maximum fluorescence emission wavelength of PBI–Tre was at 548 nm, and the changes of nanoparticles could be directly observed in the cells. PBI–Tre was coated with hyaluronic acid (HA) to improve their intracellular uptake and ability to target macrophages. The particle size of HA–PBI–Tre was 200–300 nm, and the zeta potential was −36.9 mV. The results showed that the nano-drug loading system could easily decrease the ROS level, inhibit the production of inflammatory factors, remove the accumulation of lipids in foam cells. These nanoparticles could hinder foaming progress in the RAW264. 7 cell line.